Beach erosion and recovery during consecutive storms at a steep-sloping, meso-tidal beach - Vousdoukas, Michalis (2018)
This study analyses beach morphological change during six consecutive storms acting on the meso-tidal Faro Beach (south Portugal) between 15 December 2009 and 7 January 2010. Morphological change of the sub-aerial beach profile was monitored through frequent topographic surveys across 11 transects. Measurements of the surf/swash zone dimensions, nearshore bar dynamics, and wave run-up were extracted from time averaged and timestack coastal images, and wave and tidal data were obtained from offshore stations. All the information combined suggests that during consecutive storm events, the antecedent morphological state can initially be the dominant controlling factor of beach response; while the hydrodynamic forcing, and especially the tide and surge levels, become more important during the later stages of a storm period. The dataset also reveals the dynamic nature of steep-sloping beaches, since sub-aerial beach volume reductions up to 30m3/m were followed by intertidal area recovery (–2<z 3m) with rates reaching ~10m3/m. However, the observed cumulative dune erosion and profile pivoting imply that storms, even of regular intensity, can have a dramatic impact when they occur in groups. Nearshore bars seemed to respond to temporal scales more related to storm sequences than to individual events. The formation of a prominent crescentic offshore bar at ~200m from the shoreline appeared to reverse the previous offshore migration trend of the inner bar, which was gradually shifted close to the seaward swash zone boundary. The partially understood nearshore bar processes appeared to be critical for storm wave attenuation in the surf zone; and were considered mainly responsible for the poor interpretation of the observed beach behaviour on the grounds of standard, non-dimensional, morphological parameters.202798